Improving Student Learning Outcomes Through Project-Based Learning in Islamic Religion Lessons - Aditya Firdaus, Muhammad; Jamal, Moh Yusup Saepuloh; Arifin, Bambang Samsul (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
The purpose of this study is to improve students' cognitive learning outcomes through the use of Project Based Learning. The study was conducted using Quasy Experimental research. The technique or data collection used in this study is a pretest, and posttest, In sampling using purposive sampling. The data analysis techniques used in this study are the normality test using the Shapiro-Wilk test, the t-test hypothesis testing using the Mann-Whitney test, and the N-gain test. The results in this study show that the application of the Project Based Learning learning model can improve the cognitive learning outcomes of students with an average post-test value of the experimental class of 0.76 greater than the control class with an average post-test value of 0.39. The hypothesis test results obtained a Significance value < a probability value of 0.00 < 0.05. The conclusion in this study is that the application of the Project Based Learning learning model can improve the cognitive learning outcomes of students.